Cryptographic open science: enabling secure and incentivized biomedical data sharing with web 3.0 technologies to overcome the open science dilemma - Wang, Yu; Fan, Junfeng; Bao, Zhiwei; Zhang, Sheng; Liu, Liang; Yang, Mengsu; Church, George M. (Frontiers in Blockchain, 2026)
Biomedical data underpins scientific discovery, and open science offers the potential to accelerate innovation through the unrestricted sharing of knowledge, methodologies, and datasets. However, the open science dilemma persists, as researchers hesitate to share data due to privacy concerns, intellectual property risks, and lack of recognition. Stringent data privacy regulations further compound these challenges, limiting data sharing. To address these barriers, we propose the Cryptographic Open Science (COS) framework, integrating advanced technologies for secure, privacy-preserving, and incentivized data sharing. Blockchain technology provides immutable records of data ownership and usage, enhancing transparency and trust, while smart contracts automate access controls and enforce compliance. However, blockchain alone does not prevent loss of control over plaintext data once released. COS incorporates Fully Homomorphic Encryption (FHE) to allow computations on encrypted data, ensuring end-to-end confidentiality and maintaining full ownership control. Recognizing that privacy alone does not incentivize sharing, COS introduces a crypto token-based system to create a market-driven flywheel. This system rewards contributors and aligns stakeholder interests, promoting active data sharing. By integrating blockchain, FHE, and token-based incentives, COS bridges the gap between the ideals of open science and the practical concerns of data providers, accelerating progress in fields like precision medicine and genomics.